Model Pemberdayaan Ekonomi Penyandang Disabilitas di Indonesia - Surwanti, Arni (Universitas Muhammadiyah Yogyakarta, 2014)
At the moment people with disabilities still face problem with regard to their levehood and their welfare. This research to examine the parties who have done the economic empowerment of persons with disabilities as well as the concept of economic empowerment for persons with disabilities that have been implemented This study also examines the various issues and factors that support succersful implementation of economic empowerment model person with disabilities in Indonesia This research showed in change of emplementing the economic empowerment of person with disabilities are still emphasizing the role of the Ministry of Social Affairs. Interdepartmental and inter-institutional treatment has been done, but the coordination has not been going well. The role of the private, Non Government Organization. Disable People Organization also showed a very important action. Implementation. Implementation of economic empowerment for person with disabilitas based on the laws and policies that exist both at the international, regional, national and local area. Implementasion of economic empowerment to persons with disabilities in Indonesia, still face many problem that required the presence of improvements on all side. The most dominat factor for the success of economic empowerment for persons with disabilities is the motivation of persons with disabilities, family support compatibility between the interest and the capacity to be taken in the selection process, presence of equipment and capital, the assistance of both the marketing and product development, the existence of a network of support in the community, absence of career development assistance agencies to persons with disabilities who enter the labor market.